Corncob and Sugar Beet Pulp Induce Specific Sets of Lignocellulolytic Enzymes in Penicillium Purpurogenum - Mardones-Opazo, W (Taylor and Francis Ltd., 2019)
Penicillium purpurogenum is a filamentous fungus, which grows on a variety of natural carbon sources and secretes a large number of enzymes involved in cellulose, hemicelluloses and pectin biodegradation. The purpose of this work has been to identify potential lignocellulolytic enzymes and to compare the secreted enzymes produced when the fungus is grown on sugar beet pulp (rich in cellulose and pectin) and corn cob (rich in cellulose and xylan). Culture supernatants were subjected to two-dimensional nano-liquid chromatography/tandem mass spectrometry. Using MASCOT and a genome-derived protein database, the proteins present in the supernatant were identified. The putative function in the degradation of the polysaccharides was determined using dbCAN software. The results show that there is a good correlation between the polysaccharide composition of the carbon sources and the function of the secreted enzymes: both cultures are rich in cellulases, while sugar beet pulp induces pectinases and corncob, xylanases. The eventual biochemical characterisation of these enzymes will be of value for a better understanding of the biodegradation process performed by the fungus and increase the availability of enzymes for biotechnological methods associated with this process. © 2018, © 2018 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.